2018
DOI: 10.3748/wjg.v24.i47.5379
|View full text |Cite
|
Sign up to set email alerts
|

Novel screening test for celiac disease using peptide functionalised gold nanoparticles

Abstract: AIMTo develop a screening test for celiac disease based on the coating of gold nanoparticles with a peptide sequence derived from gliadin, the protein that triggers celiac disease.METHODS20 nm gold nanoparticles were first coated with NeutrAvidin. A long chain Polyethylene glycol (PEG) linker containing Maleimide at the Ω-end and Biotin group at the α-end was used to ensure peptide coating to the gold nanoparticles. The maleimide group with the thiol (-SH) side chain reacted with the cysteine amino acid in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The unique property of graphene oxide, which binds low amounts of albumin, allows strong adsorption of proteins that are present in the plasma at low levels 62 . Other studies use magnetic NPs 63 or AuNPs 64 , 65 , which are simple to use, in biomarker detection assays, thereby saving time and money if compared with existing methods that require substantial sample processing. In addition to diagnostic screening, some therapeutic applications of NPs aim to remodel the tumour microenvironment to promote particle accumulation and penetration, and thus increase drug efficacy, and/or to sensitize tumours to a particular therapy 66 68 .…”
Section: Nps In Precision Medicinementioning
confidence: 99%
“…The unique property of graphene oxide, which binds low amounts of albumin, allows strong adsorption of proteins that are present in the plasma at low levels 62 . Other studies use magnetic NPs 63 or AuNPs 64 , 65 , which are simple to use, in biomarker detection assays, thereby saving time and money if compared with existing methods that require substantial sample processing. In addition to diagnostic screening, some therapeutic applications of NPs aim to remodel the tumour microenvironment to promote particle accumulation and penetration, and thus increase drug efficacy, and/or to sensitize tumours to a particular therapy 66 68 .…”
Section: Nps In Precision Medicinementioning
confidence: 99%
“…The sensor’s sensitivity was about 1297.1 pg, and a detection limit was found at 0.1 fg per 6 µL. In another study, Kaur et al [ 266 ] developed a screening test based on the 20 nm GNPs functionalized with a sequence of the gliadin-derived peptide, which triggers the CD. They demonstrated that this functionalized GNP with a novel peptide-based assay is helpful for pre-selecting CD, especially in high-risk pediatric populations confirmed by mucosal biopsy.…”
Section: Gold Nanoparticles As Potential Diagnostic Devices For Autoimmune Diseasesmentioning
confidence: 99%
“…A deamidated peptide sequence is derived from α -gliadin amino acids that detects the immunogenic peptide sequence acting as a trigger for CeD [ 37 ]. The AuNP peptide assay seems promising for development as a POCT as it is based on the formation of a precipitate, and there occurs a reduction in color of a positive sample in the presence of a CeD-specific autoantibody, with an overall accuracy of 86.6% [ 38 ].…”
Section: Novel Biomarkersmentioning
confidence: 99%